Review of sustainable temporary housing and reuse strategy for post-disaster architectures: current trends and strategic gaps - Berkan Kahvecioğlu; Semra Arslan Selçuk (Journal of Engineering and Applied Science)
Abstract Sustainable temporary architecture after a disaster includes temporary buildings designed to meet the emergency housing needs of disaster victims. This approach minimizes the use of waste and natural resources, reduces the environmental impact, and assumes an important responsibility to maintain the long-term ecological balance. Within the scope of this research, comprehensive and systematic results are presented by analyzing disaster issues with the “reuse” strategy, which has started to be frequently encountered in the current literature. The studies were scanned in the Web of Science and Scopus databases under the heading “Title/Abstract/Keywords,” and the data were analyzed in detail. The findings indicate research trends in the literature and gaps for future research. The results highlight the innovative approach for sustainable post-disaster temporary architecture in the context of reuse strategies and present the field’s challenges, limitations, and opportunities. This study is expected to help researchers, practitioners, experts, and politicians understand the evolutionary implications of disaster reuse strategies and develop other theoretical and practical initiatives that can be applied in this field.